2019
DOI: 10.1002/celc.201901015
|View full text |Cite
|
Sign up to set email alerts
|

Wireless, Battery‐Less Biosensors Based on Direct Electron Transfer Reactions

Abstract: Studies of direct electron transfer (DET) between enzymes and electrodes, among other reasons, are aimed at designing the simplest and most efficient biosensor designs. This direction might become especially valuable for the widespread integration of biosensors in Internet-of-Things (IoT) networks. In this Minireview, the simplicity of the design of wireless biosensors based on DET is discussed. It can be concluded that DET allows construction of wireless biosensors, which require no or only a few semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…This patch will be used in early detection and monitoring of the C0VID-19 symptoms including the recording and reporting of respiratory rate, body temperature, and ECG trace in real-time [2], [20]. The rate at which such single-use wireless biosensors will be integrated in H-IoT will largely depend on the cost, simplicity, robustness and reliability of the design [75].…”
Section: ) Biosensor Evolution For Iotmentioning
confidence: 99%
“…This patch will be used in early detection and monitoring of the C0VID-19 symptoms including the recording and reporting of respiratory rate, body temperature, and ECG trace in real-time [2], [20]. The rate at which such single-use wireless biosensors will be integrated in H-IoT will largely depend on the cost, simplicity, robustness and reliability of the design [75].…”
Section: ) Biosensor Evolution For Iotmentioning
confidence: 99%
“…The latter one forms a large group of wearable (bio)electronics, which have been extensively studied and developed within the last years. The attention drawn to the wearable electronics can be illustrated by the fact that some of the recently published reviews, concerned with this topic [ 134 , 193 , 194 , 195 , 196 , 197 , 198 , 199 ], have already reached more than 100 citations within one year.…”
Section: Application Of Msss and Msasmentioning
confidence: 99%
“…There are numerous studies of wearable biosensors for single analyte detection reported in the literature [ 193 , 194 , 196 ]. Some of the reported flexible biosensors are integrated in the MSA in combination with chemical sensors.…”
Section: Application Of Msss and Msasmentioning
confidence: 99%
“…It was noticed that oxidoreductases containing copper ion-based cofactors (e.g., laccase and bilirubin oxidase) [43], as well as NiFe and FeS hydrogenases [44,45], are also capable of DET. However, the DET phenomenon is not easily implemented-approximately only 100 out of 1700 known oxidoreductases have been shown to operate in DET applications [46,47]. Interestingly, in general, some types of oxidoreductases tend to operate by DET (e.g., metalloenzymes), while the others do not, for example, containing flavin cofactors such as FAD [46], with some exceptions, as reported recently about FAD-dependent glucose dehydrogenases (FAD-GDH) [48].…”
Section: Application Of Direct Electron Transfer (Det)-capable Oxidormentioning
confidence: 99%